2018
DOI: 10.1172/jci99257
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 upregulation elicits adaptive resistance to oncogene-targeted therapies

Abstract: Cancer cell dependence on activated oncogenes is therapeutically targeted, but acquired resistance is virtually unavoidable. Here we show that the treatment of addicted melanoma cells with BRAF inhibitors, and of breast cancer cells with HER2-targeted drugs, led to an adaptive rise in neuropilin-1 (NRP1) expression, which is crucial for the onset of acquired resistance to therapy. Moreover, NRP1 levels dictated the efficacy of MET oncogene inhibitors in addicted stomach and lung carcinoma cells. Mechanisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 52 publications
5
63
0
Order By: Relevance
“…Moreover, the level of EGFR protein, which was medium in 21_TRAR cells and very high in 28_TRAR cells, reflected the extent of EGF dependence. Several mechanisms have been implicated in the regulation of EGFR expression including suppression of SOX10 [102,103] followed by upregulation of neuropilin-1 (NRP-1)-c-Jun N-terminal kinase (JNK)-SOX2 axis [106], and SOX9 expression [107]. It is unlikely that these mechanisms are involved in the regulation of EGFR in resistant cell lines investigated in our study as (i) changes in SOX9 and SOX10 expression were not uniformly correlated with EGFR protein level, (ii) EGF deprivation was associated with downregulation of SOX10 in EGFR high 28_TRAR cells suggesting even a concurrent regulation, and (iii) TRAR cells neither expressed SOX2 protein at the detectable level nor activated JNK as shown by the phospho-protein array.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the level of EGFR protein, which was medium in 21_TRAR cells and very high in 28_TRAR cells, reflected the extent of EGF dependence. Several mechanisms have been implicated in the regulation of EGFR expression including suppression of SOX10 [102,103] followed by upregulation of neuropilin-1 (NRP-1)-c-Jun N-terminal kinase (JNK)-SOX2 axis [106], and SOX9 expression [107]. It is unlikely that these mechanisms are involved in the regulation of EGFR in resistant cell lines investigated in our study as (i) changes in SOX9 and SOX10 expression were not uniformly correlated with EGFR protein level, (ii) EGF deprivation was associated with downregulation of SOX10 in EGFR high 28_TRAR cells suggesting even a concurrent regulation, and (iii) TRAR cells neither expressed SOX2 protein at the detectable level nor activated JNK as shown by the phospho-protein array.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have revealed the importance of VEGF-NRP signaling in tumor cells, independently of its role in angiogenesis (5), its contribution to DNA repair mechanisms is significant. Of note, VEGF-NRP signaling has been implicated in drug resistance in multiple tumors, but satisfying mechanisms have been elusive (9,(48)(49)(50). Given that efficient HR is a key Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking we can distinguish mechanisms based on external and internal signals. For instance, RAF inhibitor resistant melanoma cells can upregulate the expression of neuropilin-1 (NRP1), which uses the JNK pathway to induce the expression of receptor tyrosine kinases (RTKs), specifically epidermal growth factor receptor (EGFR/ERBB1) and insulin-like growth factor receptor 1 (IGFR1), that can bypass the signaling block imposed by RAF inhibition [75]. The same mechanism applies in breast cancer cells treated with HER2 targeting drugs.…”
Section: Jnk Enhancing Resistance To Erk Pathway Inhibitors and Chemomentioning
confidence: 99%